Strenght and Conditioning Pencak Silat UKM Pagar Nusa UIN Syekh Wasil Kediri - Agung Dwi Darmawan; Ardyansyah Arief Budi Utomo; Ghon Lisdiantoro; Alifarose Syahda Zahra; Arya T Candra (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Strength and Conditioning (S&C) is an important component in preparing and improving athlete performance, especially in the sport of pencak silat which demands optimal strength, speed, endurance, and movement quality. This community service activity was carried out at the Pagar Nusa Martial Arts Student Activity Unit of UIN Syekh Wasil Kediri with the aim of improving the understanding, knowledge, and abilities of coaches and athletes in developing and implementing S&C programs that are in accordance with the characteristics of pencak silat. The methods used included material socialization and field practice assistance to 52 participants, consisting of coaches, trainers, and athletes. The results of the community service showed that before the activity began, all participants had understood the basic concepts of S&C, but did not yet understand good and correct movement techniques according to the principles of sports science. After the delivery of the material, discussion, and practice, all participants (100%) showed an increase in understanding regarding the concept of S&C, the principles of hypertrophy, biomotor, movement techniques, and the development of training programs for strength, endurance, speed, and the needs of each age category. The activity ran smoothly and received a very positive response from all participants. Thus, this service has succeeded in increasing the participants' competence in applying sports science-based Strength and Conditioning to optimize pencak silat performance.